2015
DOI: 10.1007/s00404-015-3673-6
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal imaging of anomalies of the corpus callosum: a decade of experience

Abstract: In cases of callosal anomaly suspected on ultrasound, FMRI provides greater certainty and the potential to identify significant additional anomalies. The additional information may alter or clarify prognosis and help parents to better understand the pathology, allowing for informed decisions about the pregnancy to be made. However, some cases may still be diagnosed with additional anomalies after delivery and parents should be aware of such limitations of antenatal imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…This high prevalence could be due to the fact that we included all types of ACC whereas some studies as for example Bedeschi et al () excluded hypoplasia of corpus callosum. Moreover, the ascertainment of the cases of ACC was population‐based in our study whereas it was hospital‐based in the studies for example of Shevell () and Bedeschi et al (), or the cases were recorded in a tertiary referral center (Alby et al, ; Bell et al, ; Ghi et al, ; Hetts et al, ; Kitova et al, ; Rüland et al, ; Schell‐Apacik et al, ; Tang et al, ). In the current study, 73.7% of the cases had associated anomalies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This high prevalence could be due to the fact that we included all types of ACC whereas some studies as for example Bedeschi et al () excluded hypoplasia of corpus callosum. Moreover, the ascertainment of the cases of ACC was population‐based in our study whereas it was hospital‐based in the studies for example of Shevell () and Bedeschi et al (), or the cases were recorded in a tertiary referral center (Alby et al, ; Bell et al, ; Ghi et al, ; Hetts et al, ; Kitova et al, ; Rüland et al, ; Schell‐Apacik et al, ; Tang et al, ). In the current study, 73.7% of the cases had associated anomalies.…”
Section: Discussionmentioning
confidence: 94%
“…ACC is frequently associated with other congenital defects. However the reported prevalence of associated anomalies at birth varies considerably among diverse studies, between 39.6% (Szabó et al, ) and 86.5% (Glass et al, ), as vary the type of associated anomalies reported (Alby et al, ; Ballardini et al, ; Bedeschi et al, ; Bell, Mahony, Fink, Woodrow, & Reidy, ; Ghi et al, ; Glass et al, ; Hetts, Sherr, Chao, Gobuty, & Barkovich, ; Kitova, Kitov, Milkov, & Gaigi, ; Rüland, Berg, Gembruch, Geipel, & Medicine, ; Schell‐Apacik et al, ; Shevell, ; Szabó et al, ; Tang et al, ). It has also not been established whether ACC are related to specific types of other congenital defects and there are differences in reports concerning which organ system is most often affected by associated anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, regional and remote parents often have to travel to MFM clinics, where providers are less likely to have links with the parent's local organisations, complicating referral pathways for ongoing support. While ongoing MFM follow up and ultrasounds after a diagnosis ACC may be within the management protocol, 10 this case study highlights that this may not occur for regional patients.…”
Section: Discussionmentioning
confidence: 88%
“…A report of a decade of cases included 26% identified incidentally during a third-trimester scan. 10 Given these difficulties, it is unlikely that a sonographer would be able to confirm a diagnosis of ACC at the time of a routine morphology scan but may identify an atypical appearance. The suspicion of ACC during a morphology scan warrants tertiary referral for further investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation